Order of the aro-6 and cpl-1 loci on linkage group VI of Neurospora - T J Schmidhauser (Fungal Genetics Reports, 2000)
The results reported here locate the cpl-1 locus 5.5 centimorgans to the left of the aro-6 locus on linkage group VIL of Neurospora.